RuO2 as promoter in Pt‐RuO2‐nanostructures/carbon composite, a pH‐universal catalyst for hydrogen evolution/oxidation reactions. (22nd December 2021) - Panigrahy, Sonali; Samanta, Rajib; Panda, Prajnashree; Mishra, Ranjit; Barman, Sudip
Summary: The development of new catalysts for Hydrogen evolution reaction/Hydrogen oxidation reaction (HER/HOR) is of crucial importance for the commercialization of Proton‐exchange membrane/Anion‐exchange membrane‐based renewable technologies. The sluggish HER/HOR kinetic (in base) and poor HER/HOR stability (in acid) of commercial Pt/C are the main obstacles. Interface engineering in multi‐component nanostructures is a method for enhanced electrochemical performances. We report interfaces‐engineered RuO2 ‐Pt/C as a pH‐independent catalyst for Hydrogen oxidation reaction/Hydrogen evolution reaction applications. The Hydrogen oxidation reaction/Hydrogen evolution reaction activity of RuO2 ‐Pt/C is one order magnitude higher than commercial Pt/C in base and 2.5‐fold higher in acid. It shows excellent stability in acid and base. It exhibits excellent pH tolerant HOR behavior. The i0, m of RuO2 ‐Pt/C in the base is 1833 A.g −1 RuPt which is 8‐fold higher than commercial Pt/C. The RuO2 in RuO2 ‐Pt/C makes it more active toward HER/HOR in base. Although it has similar activity in acid, its basic activity is 29‐fold higher than Ru‐Pt‐NPs/C. Hydrogen binding energy and OH binding energy are two equivalent descriptors for HOR/HER in base. HOR/HER activity of this catalyst in different 0.1 M electrolyte decreases in the sequence of Li + > Na + > K + but improved HER and decreased HOR is observed with increasing Li + ions. The [(H2 O)x ‐AM + ‐(OH)ad ] in double‐layer influences HOR/HER performance of RuO2 ‐Pt/C. This catalyst has great potential for application in PEM/AEM‐based devices. Abstract : The development of new catalysts for Hydrogen evolution reaction/Hydrogen oxidation reaction (HER/HOR) is of crucial importance for the commercialization of Proton‐exchange membrane/Anion‐exchange membrane‐based renewable technologies. The sluggish HER/HOR kinetic (in base) and poor HER/HOR stability (in acid) of commercial Pt/C are the main obstacles. Interface engineering in multi‐component nanostructures is a method for enhanced electrochemical performances.